Poemat romantyczny, epopeja, summa poetica: O Panu Tadeuszu Adama Mickiewicza - Dopart, Bogusław (Księgarnia Akademicka Publishing, 2024)
ROMANTIC POEM, EPIC, SUMMA POETICA. PAN TADEUSZ BY ADAM MICKIEWICZ The aim of this monograph is to reflect on and revise issues in the field of historical genology and literary aesthetics related to Adam Mickiewicz’s Pan Tadeusz. The author seeks to answer questions such as whether the current understanding of Pan Tadeusz meets the criteria for historically adequate interpretation, and what significance exploring the artistic and aesthetic potential of the romantic poem – as well as reconsidering the attributes of Pan Tadeusz as a national epic poem and modern epic poem – would have for a deeper understanding of the work. The discussed work presents the highest complexity of features of an open romantic form: internal diversity of compositional elements and poetic language, intense intertextuality in terms of genre-specific style and imagery, richness of references to literary tradition, and forms of reception of literature from earlier epochs. This led the author to propose a series of methodological solutions in the field of aesthetic-genological reading within the context of historically adequate literary interpretation, including a description – inspired by romantic literary criticism – of the assumptions of the so-called universal poem and romantic genre categories (epic, lyricism, drama). Projekt sfinansowany ze środków budżetu państwa, przyznanych przez Ministra Edukacji i Nauki w ramach Programu Doskonała Nauka II